PEMETAAN PENYAKIT TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS KARANGAYU TAHUN 2016-2018 - Lukya yan pratama, Arga; wulandari, fitria (STIKES Widya Husada Semarang, 2021)
Based on a preliminary survey at the Karangayu Primary Health Center, the number of pulmonary tuberculosis cases is increasing every year. This study aims to map and describe pulmonary tuberculosis by kelurahan, gender, and age group This study is a descriptive research, data collection by reviewing documents and records the data needed. The research object is all data of pulmonary tuberculosis patients in Karangayu Primary Health Center in 2016-2018. Based on research, the majority of patients with pulmonary tuberculosis located in Karangayu village, men and women have the same potential to get pulmonary TB, most patients included in the adolescent and adult age groups. Whereas based on the region, Based on the kelurahan, The number of TB sufferers in Kelurahan Bojong Salaman was more evenly distributed, in Kelurahan Salaman Mloyo TB cases incidence were found in 2017 and the number of TB sufferers in Kelurahan Cabean was lower than the other kelurahan. Areas with high population density are at risk of transmission. All age groups have the possibility of exposure to diseases, especially the adult age groups who have high mobility. Pulmonary tuberculosis disease control and prevention programs should continue